THE STRUGGLE FOR BALANCE BETWEEN WORK AND HOME: AN OVERVIEW OF ISLAMIC TEACHINGS - Dr.Farhat Nisar; Dr.Musferah Mehfooz; Dr.Musferah Mehfooz (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2022)
The flow of prioritizing work tasks with home responsibilities can become overwhelming when one or the other consistently demands greater preference. So we have to struggle for the balance between home and work so that we have equal attention to both major parts of our lives. This article aims to discuss and analyze the effect of Work Life Balance in Islamic Perspective followed by some suggestions to make balance .In addition, this article also analyzes the effect and role in mediating the employer employee relationship that may help in constructive environment on workplace for strategic conclusion of organizational progress. Discussion includes introduction, literature review of work and life balance and discussion about both employer and employee cannot find a point of balance between their careers and their families, and one is given more priority than the other which may lead to several dysfunctional outcomes of physical, mental social and moral lapses. Further some suggestions have been given to make a balance between work and family life.